Phosphate oxygen isotope ratios in vegetated riparian buffer strip soils - Sara Louise Bauke; Ye Wang; Sheila M. Saia; Carina Popp; Federica Tamburini; Stefan Paetzold; Wulf Amelung; Christian von Sperber (Vadose Zone Journal, 2022)
Abstract The oxygen isotopic composition of phosphate (δ18OP) in soils and surface water bodies has been used to trace terrestrial P inputs into aquatic ecosystems. However, enhanced biological activity in vegetated riparian buffer strips (VBSs) may lead to an alteration of δ18OP values. The objective of this study was to assess whether enhanced biological cycling of P in VBS soils can be identified using δ18OP values. For this purpose, we sampled temperate grassland soils at various depths along a VBS to grassland transect. Here, we combined sequential P soil extracts with an analysis of δ18OP values. Soil P pool concentrations tended to decrease significantly along the transect from the VBS to the grassland soils; the strength of this relationship varied with P extract, sample depth, and inorganic or organic bonding form. For the δ18OP values of the 1 M HCl‐extractable P we observed a significant negative trend along the VBS to grassland transect, indicating a tendency for accelerated rates of biological cycling of P within the VBS soil profile compared with the upslope soils. We conclude that oxygen isotope‐based assessments of P source contributions to freshwater bodies should consider the enhanced biological turnover of P in VBS soils.